Setting priorities for EU healthcare workforce IT skills competence improvement - Li, Sisi; Bamidis, Panagiotis; Konstantinidis, Stathis; Traver, Vicente; Car, Josip; Zary, Nabil (SAGE Publications, 2017)
A major challenge for healthcare quality improvement is the lack of IT skills and knowledge of healthcare workforce as well as their ambivalent attitudes towards IT. This paper identifies and prioritises actions needed to improve the IT skills of healthcare workforce across the EU. 46 experts, representing different fields of expertise in healthcare and geolocations systematically list and scored actions that would improve IT skills among healthcare workforce. The Child Health and Nutrition Research Initiative methodology was used for research priority-setting. The participants evaluated the actions using the following criteria: feasibility, effectiveness, deliverability, and maximum impact on IT skills improvement. The leading priority actions were related to appropriate training, integrating eHealth in curricula, involving healthcare workforce in the eHealth solution development, improving awareness of eHealth and learning arrangement. As the different professionals’ needs are prioritised, healthcare workforce should be actively and continuously included in the development of eHealth solutions.